2021
DOI: 10.32725/kont.2021.041
|View full text |Cite
|
Sign up to set email alerts
|

Work environment assessment instruments used in nursing

Abstract: The aim was to identify and characterize instruments for assessing the work environment of nurses. The sources of information were articles in six electronic databases. Prior to the search, a clinical question was constructed: "Which instruments are suitable for assessing the work environment of hospital nurses?" The query words were practice/work environment, nursing, scale. The search, using Boolean operators and limited to the period of 2010-2020, was performed from May to June 2020. The inclusion criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…[3][4][5] The ideal work environment is one that provides conditions for physical, mental, and social or spiritual well-being. 3 In previous studies, researchers found support for a model where nurse practice environment dimensions including nurse-physician relations, management at the department level and hospital management, and work characteristics such as social capital (networks of relationships within a society that enable its effective functioning), decision latitude (an individual's potential to control their tasks and behavior during work), and workload predict job outcome variables and nurse ratings of quality of care. 6 Structural empowerment (SE) in the workplace, as well as access to opportunities, has a direct impact on the attitude and behavior of nursing professionals.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5] The ideal work environment is one that provides conditions for physical, mental, and social or spiritual well-being. 3 In previous studies, researchers found support for a model where nurse practice environment dimensions including nurse-physician relations, management at the department level and hospital management, and work characteristics such as social capital (networks of relationships within a society that enable its effective functioning), decision latitude (an individual's potential to control their tasks and behavior during work), and workload predict job outcome variables and nurse ratings of quality of care. 6 Structural empowerment (SE) in the workplace, as well as access to opportunities, has a direct impact on the attitude and behavior of nursing professionals.…”
Section: Methodsmentioning
confidence: 99%
“…A large body of empirical literature supports the connection between the work environments that provide important context for nursing work and a variety of important patient, nurse, and organizational outcomes 3-5 . The ideal work environment is one that provides conditions for physical, mental, and social or spiritual well-being 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nurse performance is manifested through the quality of care, patient safety, and nursing services. When job satisfaction is low, the quality of care and nursing services will decrease (Janíková et al, 2021 ). Therefore, it is essential to prioritize maintaining and enhancing nurses’ job satisfaction to prevent any degradation in the quality of care and nursing services.…”
Section: Introductionmentioning
confidence: 99%
“…9 The ideal work environment provides conditions for physical, mental, and social well-being. 10 The external pressures of diminishing health-care reimbursement, increasing regulatory requirements, rising acuity and patient complexity, and increased health-care operational restrictions have a negative effect on work environments. 11 Assessment of work environment is essential indicators of hospital management and can be applied to workforce planning and identifying nursing profession needs.…”
Section: Introductionmentioning
confidence: 99%